Havana and the Atlantic in the sixteenth century - Fuente, Alejandro de la, 1963- (Envisioning Cuba., 2008)
De la Fuente provides the first examination of the transformation of Havana into a vibrant Atlantic port city and the fastest-growing urban center in the Americas in the late sixteenth century. He shows how local ambitions took advantage of the imperial design and situates Havana within the slavery and economic systems of the colonial Atlantic.